How to do things with legal doctrine - Schlag, Pierre; Griffin, Amy J. (Chicago : The University of Chicago Press, 2021)
Legal doctrine - the creation of doctrinal concepts, arguments, and legal regimes built on the foundation of written law - is the currency of contemporary law. Yet law students, lawyers, and judges often take doctrine for granted, without asking even the most basic questions. 'How to Do Things with Legal Doctrine' is a sweeping and original study that focuses on how to understand legal doctrine via a hands-on approach.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 6, 2021).
Keywords: Law -- Methodology; Jurisprudence; Law; Jurisprudence & general issues